Determining the Factors of the Employees’ Intention to Stay or Leave in the Slovak’s SMEs - Rozsa Zoltan; Formánek Ivo; Maňák Radim (International Journal of Entrepreneurial Knowledge, 2019)
A large number of Slovak small and medium enterprises (SMEs) are confronted with often-leaving employees. This situation can have a devastating effect; thus, the ability to predict and early detect the employees’ intention to stay or leave to another organisation provides them with a competitive advantage.